Closing the Gap : The State of Social Safety Nets 2017 - World Bank Group (World Bank, Washington, DC, 2017)
There is an increasing global focus on social protection. For the first time social protection (SP) is part of a comprehensive Sustainable Development Goals (SDG) agenda. As a reflection of this global focus, there has been an explosion of activity in social safety nets programs around the world. The number of developing countries with social safety nets (SSN) doubled in the last two decades from 72 to 149 countries There has also been an increasing complexity of SSN systems or programs in pursuit of greater results. A growing commitment to SSN is also evident in the fact that countries tend to spend more on SSN over time. A growing commitment to SSN is also evident in the fact that countries tend to spend more on SSN over time. More needs to be done as significant gaps in coverage remain around the globe. Much effort continues to be put into experimenting with new SSN instruments, and learning what works, especially with respect to promoting productive inclusion.